Karakteristik Fisik Peneluran Chelonia mydas, Linn. 1758 di Kaimana-Papua Barat - Zeth Parinding; Sambas Basuni; Herry Purnomo; Nandy Kosmaryandi; Yusli Wardiatno (Institut Pertanian Bogor, 2015)
Venu Island Wildlife areas, Kaimana-West Papua is one of the places for nesting of Chelonia mydas, Linn. 1758/Green Turtles/Jelepi. Thus, This study was conducted to identify the physical characteristics of Jelepi nesting in the Venu Island Wildlife areas, Kaimana-West Papua. Based on the analysis of the main components bi-plot of the physical characteristics of the main factors were found nesting and landing Jelepi, among others: Temperature sand at depth ≤30 cm (X ̅=27.42 C ± stdev 0,47 C), lighting at 11.0013.00 (X ̅=229.25lux ± stdev 326.50lux), building areas (X ̅=3.18 m2 ± stdev 16,74 m2), medium sand fraction in depth ≤30 cm (X ̅=39.86 ± stdev 16.11), and the number of holes nesting Jelepi (X ̅=1.52 nest ± stdev 1.12 nest).